a Evaluasi Kandungan Nutrisi dan Kualitas Fisik Pakan Silase Lengkap Menggunakan Berbagai Jenis Hijauan - Wijayanti, Desna; Astuti, Puji; Nurtanti, Ina; Anifitiatiningrum, Anifitiatiningrum (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2025)
Background: The year-round availability and nutritional adequacy of forage for ruminants can be effectively addressed through the development of complete feed silage, as conventional forage sources often lack sufficient crude protein to meet dietary requirements. Purpose: The aim of the study was to determine the differences in the different types of forage used in making complete feed silage on physical quality and nutritional content. Methods: The research method used a completely randomized design experiment consisting of 3 treatments and 4 replications. The treatment consisted of P1: 50% concentrate + 50% odot grass, P2: 50% concentrate + 50% corn stalks and P3: 50% concentrate + 50% kolonjono grass. Parameters measured were physical quality (color, aroma, texture and presence of mushrooms) and nutritional content consisting of dry matter, organic matter, crude protein and crude fiber). Data were analyzed using ANOVA and continued with Duncan. Results: The results showed that complete feed silage using different forages produced good physical quality the color is yellowish green to brownish green, the aroma is slightly sour to sour, the texture is hard to slightly soft and not moldy. Conclusion: complete feed silage, using corn stalks produces the best crude protein, namely 14.11%.